2023
DOI: 10.7759/cureus.36574
|View full text |Cite
|
Sign up to set email alerts
|

Viral Shedding and Persistence of Anosmia and Ageusia in an Asymptomatic SARS-CoV-2 Infection

Abstract: The novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), first identified in the region of Wuhan, China is responsible for the ongoing pandemic of coronavirus disease-19 (COVID-19) that has been a part of our life for almost three years now. Although there have been multiple reports of prolonged viral shedding in people with severe disease, viral shedding lasting for extended periods can occur in patients with less serious clinical insults or even asymptomatic individuals. Herein, we report a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…PASC cases have predominantly been documented among patients who experienced severe SARS-CoV-2 infections and/or were hospitalized during the acute phase [ 8 , 9 ]. It has, however, been reported that asymptomatic and mild Covid-19 symptomatic individuals also developed PASC [ 10–13 ].…”
Section: Introductionmentioning
confidence: 99%
“…PASC cases have predominantly been documented among patients who experienced severe SARS-CoV-2 infections and/or were hospitalized during the acute phase [ 8 , 9 ]. It has, however, been reported that asymptomatic and mild Covid-19 symptomatic individuals also developed PASC [ 10–13 ].…”
Section: Introductionmentioning
confidence: 99%